Kurdish Women’s Experiences of Health Care Needs with Breast Cancer: A Qualitative Interview Study From the Kurdistanregion of Iraq (Indian Journal of Public Health Research & Development, 2020)
Purpose: Poor accessibility to health services, lack of sufficient health-related information, and problemsrelated to socioeconomic, infrastructural, geographical, and ethnic variations may lead to delayed diagnosisand treatment of breast cancer. Through real experiences of women patients admitted in an oncologydepartment, we aimed to identify and better understand the health care needs that women with breast cancerface during their treatment journey.Method: The present qualitative study was carried out using inductive content analysis. Data was obtainedfrom 12 women in oncology departments in two different hospitals in the city of Erbil, in the KurdistanRegion of Iraq. In-depth semi-structured interviews were conducted and thematic analysis of the collecteddata resulted in the extraction of themes and subthemes.Results: Analyzing the transcripts of the interviews revealed four main themes: Emotional, spiritual, andpsychological needs; Physical and body image change needs and Information needsConclusions: During their search for health care services, patients with breast cancer in the KurdistanRegion of Iraq are faced with Understanding the phenomenon of ‘living with breast cancer’ seems to becrucial for nurses to help women with breast cancer to find themselves in confronting the consequences ofthe changes associated with the illness. That needs to be resolved in order to enable delivering of a higherquality of health care to these patients.
Keywords: Breast neoplasm; qualitative research; oncology women; Kurdistan; Iraq.